Pengaruh budaya organisasi, lingkungan kerja dan kompensai terhadap kinerja karyawan hotel insumo palace - Mifta Wahyu Putra; Anita Sumelvia Dewi; Erwin Syahputra (Fakultas Ekonomi dan Bisnis, Universitas Islam Raden Rahmat Malang, 2023)
This study aims to determine: (1) the influence of organizational culture on employee performance, (2) the effect of the work environment on employee performance, (3) the effect of compensation on employee performance (4) the influence of organizational culture, work environment and compensation on employee performance. This type of research uses a quantitative approach. The sample of this research is the employees of Hotel Insumo Palace Kediri as many as 60 respondents. The sampling technique used was purposive sampling. The data collection technique uses a questionnaire that has been tested for validity and reliability. The data analysis technique used is multiple linear regression. The results of the study at a significance level of 5% indicate that: (1) there is no partial and significant influence of Organizational Culture on Employee Performance. The sig value is 0.064 > 0.05. (2) there is a partial and significant influence of the Work Environment on Employee Performance. The value of sig 0.000 < 0.05. (3) there is a partial and significant effect of compensation on employee performance. The value of sig 0.000 < 0.00. (4) the simultaneous influence of Working Period, Work Environment and Employee Engagement on Employee Performance. The value of sig 0.000 < 0.05. the regression equation is obtained with the value of Y = 4.249 +(- 0.384)X1 + 0.93X2 + 1.595X3